Dinamika Pembatalan Hak Atas Tanah: Sebuah Tinjauan Yuridis Komprehensif - Asrullah Asrullah; Kairuddin Karim; Muh. Darwis; Muh. Akbar Fhad Syahril (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This study examines the factors causing the cancellation of land rights due to administrative defects and the mechanism for cancellation. Using normative and empirical juridical approaches, this study examines Agrarian law regulation and practice in the field. As a result, cancellations often occur due to falsification of data and misuse of identity, affecting the real landowner. The settlement of the case at the Pinrang Regency Land Agency Office refers to Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional RI No. 21 Tahun 2020.